Does the gradient‐regulated connection improve the description of correlated metal bond properties?. Issue 6 (27th November 2018) - Mostafa, Rola; Brémond, Éric; Adamo, Carlo; Ciofini, Ilaria; Morell, Christophe; Chermette, Henry
Abstract: Gradient‐regulated connection (GRAC) is a generalized gradient approximation exchange density functional designed by combining the revPBE and PW91 exchange functionals to impose their behaviors in the slowly‐ and fast‐varying density regions, respectively. Such a construction allows one single density functional to accurately estimate both covalent and weak interactions occurring in main‐group‐based molecular systems. For the first time, the assessment of the performance of the GRAC exchange functional is extended to the modeling of various metal bond energy and structure properties. This assessment shows that when GRAC is coupled with the Perdew, Burke, Ernzerhof (PBE) correlation, the resulting exchange‐correlation density functional is an excellent alternative to global hybrids to model bond dissociation energy, atomic electronic excitation energy, and bond length structure properties of single‐reference metal bonds. It also shows that coupling with the Tognetti, Cortona, Adamo (TCA) correlation constitutes a robust approach to tackle energy bond properties of organometallic complexes with multi‐reference character. Abstract : Gradient‐regulated connection (GRAC) is a generalized gradient approximation exchange density functional designed by merging the revPBE and PW91 exchanges to impose their behaviors in the slowly‐ and fast‐varying density regions, respectively. When coupled with the PBE or TCA correlation, GRAC is an excellent alternative to global hybrids to model bond dissociation energy, atomic electronic excitation energy, and bond length structure properties of single‐ or multi‐reference character metal bonds.